A hybrid processing method for high performance hydrogen-selective silica membranes - Nair, Balagopal; Gopalakrishnan, S.; Yoshino, Y.; Nomura, M.; Nakao, S. (Elsevier B.V, 2007)
Development of high performance hydrogen-selective inorganic membrane has become an important requisite for the production of hydrogen, an energy carrier that could cater the ongoing energy revolution. This paper describes a novel, hybrid method to process high performance hydrogen perm-selective membranes by the rapid CVD modification of a sol-gel silica layer. The initial N2 permeance values through a membrane were brought down by four orders of magnitude to 2.741010 mol m2 s1 Pa1 within 5 min of CVD, while maintaining the H2 permeance values as high as 6.43107 mol m2 s1 Pa1 (H2/N2 = 2300). It is likely that the reduction in the CVD zone thickness achieved by the presence of pre-existing sol-gel silica layer is the reason for the rapid modification of the pore structure to high performance membranes.